Pengaruh Perencanaan Anggaran, Kualitas Sumber Daya Manusia dan Pelaksanaan Anggaran terhadap Penyerapan Anggaran pada Organisasi Perangkat Daerah Provinsi Banten - Anisa, Indi Zaenur (JURNAL RISET AKUNTANSI TIRTAYASA, 2017)
This study aims to find out The Influence of Budget Planning, Quality of Human Resources and Budget Implementation Towards Budget Absorption in Local Government of Banten Province. The object of research include the manajer of planning, financial manager and the manager technical Account Officer, used Purposive sampling. Data analysis techniques is multiple regression used SPSS 20.0. The result showed that Budget Planning, Quality of Human Resources and Budget Implementation has significant positive impact towards Budget Absorption in Local Government of Banten Provincein Local Government of Banten Province.Keywords: Budget Planning, Quality of Human Resources, Budget Implementation, Budget Absorption